Recovery of Percent Vital Capacity by Breathing Training in Patients With Panic Disorder and Impaired Diaphragmatic Breathing. (September 2017) - Yamada, Tatsuji; Inoue, Akiomi; Mafune, Kosuke; Hiro, Hisanori; Nagata, Shoji
Slow diaphragmatic breathing is one of the therapeutic methods used in behavioral therapy for panic disorder. In practice, we have noticed that some of these patients could not perform diaphragmatic breathing and their percent vital capacity was initially reduced but could be recovered through breathing training. We conducted a comparative study with healthy controls to investigate the relationship between diaphragmatic breathing ability and percent vital capacity in patients with panic disorder. Our findings suggest that percent vital capacity in patients with impaired diaphragmatic breathing was significantly reduced compared with those with normal diaphragmatic breathing and that diaphragmatic breathing could be restored by breathing training. Percent vital capacity of the healthy controls was equivalent to that of the patients who had completed breathing training. This article provides preliminary findings regarding reduced vital capacity in relation to abnormal respiratory movements found in patients with panic disorder, potentially offering alternative perspectives for verifying the significance of breathing training for panic disorder.